Konsep Akhlak Menurut Ibnu Miskawaih dan Penerapannya dalam Pendidikan Karakter Islami - Salamah, Salamah (Jurnal Ilmiah Guru Madrasah, 2025)
This study aims to examine in depth the concept of morals according to Ibn Miskawaih and its relevance to the application of Islamic character education in the modern era. Ibn Miskawaih is one of the important figures in classical Islamic ethical thought who sought to combine Greek philosophy, particularly Aristotelian thought, with Islamic moral principles derived from the Qur'an and Sunnah. In his work Tahdzīb al-Akhlāq wa Tathhīr al-A‘rāq, Ibn Miskawaih defines akhlak as a state of mind that drives a person to act spontaneously without rational consideration, but this state is formed through continuous moral training and education. His concept of morals emphasizes the balance between three main forces within humans, namely rationality (al-quwwah al-‘aqliyyah), anger (al-quwwah al-ghadhabiyyah), and lust (al-quwwah al-shahwiyyah). This balance gives rise to four main virtues: wisdom, courage, purity, and justice. In the context of Islamic character education, Ibn Miskawaih's thinking can be applied through habituation, exemplary behavior, spiritual guidance, and self-control. The results of this study indicate that Ibn Miskawaih's concept of akhlak is highly relevant for shaping a generation that is faithful, knowledgeable, virtuous, and capable of facing moral challenges in the era of globalization.